PERANCANGAN DAN IMPLEMENTASI SISTEM PENGUKURAN KINERJA DENGAN METODE INTEGRATED PERFORMANCE MEASUREMENT SYSTEMS (Studi Kasus: Jurusan Teknik Mesin Universitas Mataram) - Bambang Syairuddin; Patdono Suwignjo; I Made Suartika (Institute of Research and Community Outreach - Petra Christian University, 2007)
To assure the quality of education in the Department of Mechanical Engineering, we need to design an integrated performance measurement system. For that purpose, we used the IPMS (Integrated Performance Measurement Systems) method. Using the IPMS method, Key Performance Indicators (KPIs) of the Department of Mechanical Engineering were determined by pursuant to stakeholder requirement through four steps. Those are identifying the stakeholder requirement, external monitor, stipulating objectives, and identification of KPIs. Performance measurement system with the IPMS method in the Department of Mechanical Engineering of Mataram University can be identified into 38 KPIs grouped in 9 criterias of performance of the Department of Mechanical Engineering, that are curriculum, student, financial, human resources, administration academic, teaching and learning, alumnus, evaluation and operation, and external party. Abstract in Bahasa Indonesia : Untuk menjamin kualitas pendidikan di Jurusan Teknik Mesin, diperlukan sebuah rancangan sistem pengukuran kinerja (SPK) yang terintegrasi dengan metode IPMS (Integrated Performance Measurement Systems). Dengan metode IPMS, Key Performance Indicators (KPI) Jurusan Teknik Mesin ditentukan berdasarkan stakeholder requirement melalui empat tahapan yaitu; identifikasi stakeholder requirement, external monitor, penetapan objectives, dan identifikasi KPIs. Hasil perancangan SPK di Jurusan Teknik Mesin Universitas Mataram, dapat mengidentifikasi 38 KPIs yang dikelompokkan dalam 9 kriteria kinerja Jurusan Teknik Mesin, yaitu; kurikulum, mahasiswa, finansial, SDM, administrasi akademik, proses pembelajaran, alumni, evaluasi dan pengendalian, dan external party. Kata Kunci : Sistem Pengukuran Kinerja, IPMS, Teknik Mesin Unram.